2019
DOI: 10.1007/s12630-019-01342-7
|View full text |Cite
|
Sign up to set email alerts
|

Right upper lobe anatomy revisited: a computed tomography scan study

Abstract: Background The double lumen tube (DLT) has become the most popular way to isolate the lungs for thoracic surgery. The variable anatomy of the right main stem bronchus (RMSB) seems to be the main reason clinicians are unwilling to use the right-sided DLT (R-DLT). The factors that could compromise the adequate ventilation of the right lung are mostly the variable length of the RMSB and the misalignment of the lateral orifice of the R-DLT in regard to the right upper lobe bronchus (RULB). The objectives of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
1
12
0
Order By: Relevance
“…The results of our study showed a much higher rate (52.3%) of RMSB length less than 23 mm (63.5% in women, 42.8% in men) in our patients. This percentage is comparable with that (50%) in Korea patients, and differs from that (25%) in Canadian patients [4,13]. The Kim's study had a very small number of cases, inversely, our study included the greatest number of patients (n = 2093) of all relevant studies except for our own previous study, as listed in Table 1, so the percentage is convincing.…”
Section: Plos Onesupporting
confidence: 68%
See 3 more Smart Citations
“…The results of our study showed a much higher rate (52.3%) of RMSB length less than 23 mm (63.5% in women, 42.8% in men) in our patients. This percentage is comparable with that (50%) in Korea patients, and differs from that (25%) in Canadian patients [4,13]. The Kim's study had a very small number of cases, inversely, our study included the greatest number of patients (n = 2093) of all relevant studies except for our own previous study, as listed in Table 1, so the percentage is convincing.…”
Section: Plos Onesupporting
confidence: 68%
“…Different mean RMSB lengths ranged from 12 to 25.5 mm had been described in previous publications [9][10][11][12][13] (Table 1). In these studies, aside from different methods, such as in vivo fiberoptic bronchoscopy, autopsy study and cast study as well as computed tomography (CT) scan, were used to measure the RMSB length, the definition of the RMSB length were ambiguous.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Benumof et al [34] de ned the margin of safety of Rusch RDLT intubation as the length of the RUL-VS minus RUL diameter. Kim JH et al [17,35] suggested that LDLT should be considered if the distance between the tracheal carina and the distal edge of the RUL bronchus is less than 23 mm. However, the above studies did not take into account the design and size of different brands of DLTs.…”
Section: Discussionmentioning
confidence: 99%